1994
DOI: 10.4315/0362-028x-57.3.204
|View full text |Cite
|
Sign up to set email alerts
|

Growth of Listeria monocytogenes, Aeromonas hydrophila, and Yersinia enterocolitica on Vacuum and Saturated Carbon Dioxide Controlled Atmosphere-Packaged Sliced Roast Beef

Abstract: The growth of Listeria monocytogenes, Aeromonas hydrophila and Yersinia enterocolitica on sliced roast beef packaged under vacuum or saturated CO2 controlled atmosphere conditions was measured. At −1.5°C, the pathogens declined in numbers in the controlled atmosphere packs but were able to grow under vacuum packaging. At 3°C, growth occurred, with maximum numbers being reached at the end of the product's storage life. The increased shelf life of sliced roast beef incubated under a carbon dioxide controlled atm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
55
0
6

Year Published

1998
1998
2013
2013

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(64 citation statements)
references
References 0 publications
3
55
0
6
Order By: Relevance
“…The second one (model #7) was proposed by Koutsoumanis et al (2004) for temperatures ranging from 4 to 30°C, pH ranging from 4AE24 to 6AE58 and water activities ranging from 0AE900 to 0AE993. For the evaluation of these probability models, we considered that growth or no growth were Kaya and Schmidt (1989) 3 3 Grau and Vanderlinde (1990, 1992 88 88 Chen and Shelef (1992) 8 8 Grant et al (1993) 8 8 Hudson and Mott (1993c), Hudson et al (1994) …”
Section: Growth Modelsmentioning
confidence: 99%
“…The second one (model #7) was proposed by Koutsoumanis et al (2004) for temperatures ranging from 4 to 30°C, pH ranging from 4AE24 to 6AE58 and water activities ranging from 0AE900 to 0AE993. For the evaluation of these probability models, we considered that growth or no growth were Kaya and Schmidt (1989) 3 3 Grau and Vanderlinde (1990, 1992 88 88 Chen and Shelef (1992) 8 8 Grant et al (1993) 8 8 Hudson and Mott (1993c), Hudson et al (1994) …”
Section: Growth Modelsmentioning
confidence: 99%
“…In the food chain, the bacterium is exposed to various stresses through sanitation, disinfection, heating, cooling, and the addition of food additives and preservatives. L. monocytogenes tolerates a wide variety of stressful conditions and is able to grow at temperatures as low as Ϫ1.5°C (24), in the pH range of 4.3 to 9.6 (17,51), in water activity down to 0.90 (40), and under anaerobic atmospheres (51).…”
mentioning
confidence: 99%
“…Growth of Y. enterocolitica was reported in 100% CO 2 on roast beef at 3°C (Hudson et al 1994), lamb at 5°C (Doherty et al 1995;Sheridan and Doherty 1994) and beef (Gill and Reichel 1989), while growth was not detected in lamb in either 100% CO 2 or CO 2 /O 2 (20/80) at 0°C (Doherty et al 1995;Sheridan and Doherty 1994). However, the latter authors also observed multiplication of the same strain at 1°C in an atmosphere of CO 2 /N 2 (50/50).…”
Section: Introductionmentioning
confidence: 98%